1974
DOI: 10.1128/iai.9.1.27-33.1974
|View full text |Cite
|
Sign up to set email alerts
|

Streptolysin O Inhibition of Neutrophil Chemotaxis and Mobility: Nonimmune Phenomenon with Species Specificity

Abstract: The effects of streptolysin 0 (SO) (1 to 4 hemolytic units) on the mobility of neutrophilic leukocytes from humans, baboons, sheep, and rabbits were compared. After SO treatment, chemotaxis and random mobility of human neutrophils were markedly suppressed, baboon and sheep neutrophils were partially suppressed, and rabbit neutrophils were unaffected and demonstrated normal chemotaxis and mobility. The amounts of SO used in the mobility studies caused no leukocyte lysis or trypan blue uptake by human, baboon, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Only one-third of the leukocytes pretreated with low doses of AH were able to migrate toward ZAS as compared with control cells. Others (3,32) reported similar data for SLO. Treatment of human neutrophils with as little as 0.12 HU50 of SLO per ml reduced chemotaxis to 8 to 46% of that of control cells.…”
Section: Measurement Of Phagocytosis By Direct Plate Countssupporting
confidence: 53%
“…Only one-third of the leukocytes pretreated with low doses of AH were able to migrate toward ZAS as compared with control cells. Others (3,32) reported similar data for SLO. Treatment of human neutrophils with as little as 0.12 HU50 of SLO per ml reduced chemotaxis to 8 to 46% of that of control cells.…”
Section: Measurement Of Phagocytosis By Direct Plate Countssupporting
confidence: 53%
“…SLO is produced by group A streptococci both in vitro and in vivo, but the factors which determine the synthesis and release of SLO are not understood (1). The tissue-damaging and cytolytic properties of SLO (1) and the ability of sublytic concentrations of SLO to inhibit chemotaxis of human neutrophilic leukocytes (2,33) suggest that SLO may contribute to the pathogenesis of group A streptococcal infections in humans. High titers of anti-SLO antibodies which are indicative of a recent group A streptococcal infection of the pharynx and a good response to streptococcal antigens are a characteristic feature of rheumatic heart disease, an often fatal nonsuppurative sequel to streptococcal pharyngi-tis.…”
mentioning
confidence: 99%
“…Interestingly, both SLO and pneumolysin have been reported to inhibit neutrophil migration. 41,42 In contrast, Johnson et al 43 reported that low concentrations of pneumolysin stimulated neutrophil migration. Neutrophils and keratinocytes have been shown to interact in wound-healing processes.…”
Section: Discussionmentioning
confidence: 98%